New Legal Regulation of the Administrative Justice in the Slovak Republic - Vačok, Juraj (Public Governance, Administration and Finances Law Review, 2020)
Administrative justice is a very strong element of control of public administration. Its decisions not only control but also guide the future directions in an application of particular legal norms. The author evaluates the new changes of administrative justice in the Slovak Republic. He points out the main changes in comparison with the previous legal regulation and tries to evaluate them. He points out that it is too early to evaluate the whole new legal regulation. Despite this fact, he states that it is possible to make a partial evaluation on the basis of a result and experiences acquired to this time.